A tale of be(com)ing a Sport Nutritionist: Reflexive insights from a researcher-practitioner entering the field - Meghan R.N. Bentley; Laurie B. Patterson; Susan H. Backhouse (PLoS ONE, 2025)
Qualitative research can facilitate an understanding of the richness and complexity of human experience, shedding light on multifaceted relationships that exist within sporting environments. Within the field of sport nutrition, such immersive methods are not commonplace. Yet could offer a significant contribution to our understanding and help practitioners navigate their values and identity within the challenging world of high-performance sport. The first author, a neophyte sport nutrition researcher-practitioner, reflects upon her experience over a four-year period of integrating into a high-performance organisation and embarking upon a research programme and career as a sport nutritionist. Drawing on field notes, reflexive journal entries, and regular research team discussions, three moments of discovery are shared: 1) Navigating the transition into high-performance sport, 2) Understanding the performance pressures and emotional burden experienced by athletes, and 3) Negotiating collaboration in the nutritionist-athlete relationship. Through this confessional tale, we recognise the development of a sport nutritionist’s values and identity is unlikely to be smooth or linear. Instead, it may be a bumpy voyage of self-inquiry and discovery, shaped by diverse cultural experiences. To help future sport nutrition researcher-practitioners entering the field, we offer three meaningful development activities including 1) engaging in reflexive practice with critical friends to explore the dilemmas and uncertainties that may impact personal and professional development, 2) fostering intellectual candour when engaging in reflexive practice to facilitate self-discovery and growth, and 3) prioritise reading the growing literature on sport and organisational culture to inform and influence the delivery of sport nutrition practice.